THE REPUTATIONAL LIABILITY OF A HIGHER EDUCATION INSTITUTION: PROBLEMS, EXPERIENCE, PROSPECTS - Semyon D. Reznik; Tatyana A. Yudina (Высшее образование в России)
Abstract. The Russian higher education institutions found themselves in difficult conditions which characterize the development of higher school in our country today. They are forced to be not only socially responsible, but also reputationally responsible subjects of education market. The purpose of the article is studying of the reputational liability of a higher educational institution as an important characteristic of its management system. The authors dwell on the content and structure of the reputational liability of educational institution. On the example of a concrete university an experience of forming the reputational liability of a higher education institution is viewed. Technologies to raise the reputational liability are described. The authors come to a conclusion that forming and raising of the reputational liability of Russian higher education institutions should have a long-term character that can be reached by the development of the corresponding development strategy.